Losing its ground: A case study of fast declining populations of a ‘least-concern’ species, the bonnet macaque (Macaca radiata) - Erinjery, Joseph J.; Kumar, Shanthala; Kumara, Honnavalli N.; Mohan, K.; Dhananjaya, Tejeshwar; Sundararaj, P.; Kent, Rafi; Singh, Mewa (PLOS ONE, 2017)
The populations of many species that are widespread and commensal with humans have been drastically declining during the past few decades, but little attention has been paid to their conservation. Here, we report the status of the bonnet macaque, a species that is considered ‘least-concern’ for conservation. We show that the widely ranging rhesus macaque is expanding its range into the distributional range of the bonnet macaque, a species endemic only to southern India. Bonnet macaques have very low abundance in forests of all types indicating that it is not a typically forest dwelling species. The traditionally preferred habitats of bonnet macaques have been Hindu temples/ tourist spots but our data reveal that nearly 50% population of bonnet macaques has disappeared from such previously occupied spots. Another preferred habitat of bonnet macaques has been roadsides with abundant Ficus trees adjoining croplands. We found that between 2003 and 2015, the roadsides have drastically changed where vegetation has been replaced with barren lands and urbanization. Consequently, the populations of bonnet macaques have declined by more than 65% over the past 25 years, and by more than 50% between 2003 and 2015 alone. We, therefore, conclude that this ‘least-concern’ species is actually facing serious conservation challenges. We also identify a few places such as small hillocks with natural vegetation and a few temples/tourist spots which are likely to remain stable and thus can serve as ‘bonnet macaque conservation reserves’. Since the bonnet macaque shares many traits with several other commensal and ‘low-risk’ species, it can serve as a model for the development of long-term conservation strategies for most such species.